Tuberculous myocarditis presenting as a refractory ventricular tachycardia of biventricular origin - Gautam, MP; Sogunuru, G; Subramanyam, G; Viswanath, RC (Journal of College of Medical Sciences-Nepal, 2012)
Ventricular tachycardia (VT) is one of the difficult clinical problems for the physician. Its evaluation and treatment are complicated because of its life-threatening nature and urgent need of rapid management. Any process that creates myocardial scar tissue could be the substrate for ventricular tachycardia. The coronary artery disease is the most common cause of myocardial scar. The dilated cardiomyopathies, hypertrophic cardiomyopathy, right ventricular dysplasia, Chagas disease, sarcoidosis, myocarditis including tubercular and other chronic granulomatous conditions and surgical incisions in the ventricle also can create myocardial scar and can lead to ventricular tachycardia. Occasionally, the arrhythmia may be well-tolerated, but in most of the situations it is associated with grave, life-threatening hemodynamic compromise. Regardless of the arrhythmia mechanism, the severity of clinical symptoms and hemodynamic compromise determines the urgency with which VT must be treated. Rarely, patients present with repetitive runs of nonsustained or sustained VT despite the medical treatment and poorly respond to the conventional treatment. Such refractory VT may cause a tachycardia-induced cardiomyopathy in long run. In such cases, long-term management also include looking beyond the VT and work up for the possible and treatable cause of VT. Here we are presenting a case report of a young patient with tubercular myocarditis who has presented to us with recurrent ventricular tachycardia of both right bundle and left bundle branch block morphology and LV dysfunction. A review of literature has been carried out on causes and management of refractory VT. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 60-66 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6686